Ultralow-carbon bainite steel for 440 MPa ocean engineering and preparation method of ultralow-carbon bainite steel

By designing the chemical composition and manufacturing process of ultra-low carbon bainitic steel, the problems of insufficient thickness and welding performance of 440MPa grade hull steel have been solved, realizing high-strength, low-temperature toughness and excellent welding performance of marine engineering steel, thus broadening the application range and reducing production costs.

CN119351888APending Publication Date: 2025-01-24CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411695789.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing 440MPa grade hull steel has limited adaptability to the maximum thickness specification and poor weldability, which cannot simultaneously meet the requirements of strength and weldability, resulting in increased production costs and limited application scope.

Method used

The chemical composition of ultra-low carbon bainitic steel is designed, including C: 0.01-0.03%, Mn: 0.5%-1.0%, Mo: 0.5%-0.8%, Nb: 0.02%-0.05%, Ni: 1.0%-2.0%, Cr: 0.8%-1.2%, Ti: 0.010%-0.020%, and Al: 0.10%-0.30%. Through hot metal pretreatment, converter smelting, LF refining, RH refining, continuous casting, controlled rolling and cooling, and tempering heat treatment, the impurity content is controlled to prepare granular bainitic steel. The granular bainite contains dispersed nano-sized Ni3Al precipitates.

Benefits of technology

A high-strength, low-temperature toughness steel plate with a thickness of 120mm has been developed. It has good weldability, can be welded at room temperature without preheating, and has excellent weld joint performance. This solves the shortcomings of existing technologies in terms of thickness and weldability, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351888A_ABST
    Figure CN119351888A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ocean engineering structural steel thick plates, in particular to 440 MPa grade ultra-low carbon bainite steel and a preparation method thereof. The invention relates to 440 MPa grade ultra-low carbon bainite steel for ocean engineering. The 440 MPa grade ultra-low carbon bainite steel comprises the following chemical components in percentage by weight: 0.01 to 0.03 percent of C, 0.5 to 1.0 percent of Mn, 0.5 to 0.8 percent of Mo, 0.02 to 0.05 percent of Nb, 1.0 to 2.0 percent of Ni, 0.8 to 1.2 percent of Cr, 0.010 to 0.020 percent of Ti, 0.10 to 0.30 percent of Al and the balance of iron and inevitable impurities. The steel can adapt to production of a steel plate with the thickness of 120 mm to the maximum, and has good welding performance while meeting the strength requirement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of marine engineering structural steel thick plates, and in particular to a 440MPa grade ultra-low carbon bainite steel and a preparation method thereof. Background Art

[0002] At present, in the shipbuilding industry, there are extremely stringent requirements for the strength and welding performance of hull materials. The C content of the 440MPa grade hull steel commonly found on the market is usually between 0.08% and 0.14%, and the total content of alloy elements exceeds 3.5%; this design of C content and alloy content not only improves the strength of steel, but also brings many challenges to welding performance. On the one hand, the C element is prone to form hard and brittle carbides during the welding process, which not only reduces the toughness of the welded joint, but also greatly increases the risk of thermal cracking. On the other hand, the uneven distribution of alloy elements and the thermal stress generated during the welding process make the embrittlement of the welded joint more serious, and the control of the welding process becomes more complicated. In order to avoid the occurrence of these welding defects, it is usually necessary to preheat the steel before welding, and the temperature is generally controlled between 80℃ and 100℃. However, this preheating process not only increases the complexity of the production process, but also greatly increases the manufacturing cost of the ship. According to industry statistics, the cost of welding process accounts for as much as 25% to 45% of the total ship construction cost. The increase in welding difficulty has directly led to a significant increase in material application costs, which has seriously restricted the economic benefits of the shipbuilding industry.

[0003] Ultra-low carbon bainitic steel (ULCB) is a new type of high-strength, high-toughness, multi-purpose steel developed internationally in recent years. The alloy design concept of ultra-low carbon bainitic steel is different from that of the original high-strength low-alloy steel. By significantly reducing the carbon content, the influence of carbon on the toughness and welding performance of steel is eliminated. At present, ultra-low carbon bainitic steel has been widely used in oil pipelines, transportation buildings and marine facilities.

[0004] Because the current 440MPa grade steel alloy system has uneven cross-sectional properties when producing steel plates with a thickness of more than 80mm, the yield strength surplus and toughness level at the center are small, resulting in poor results for 440MPa grade steel in marine engineering equipment in extremely cold environments. In addition, the -40℃ impact energy performance of the coarse-grained heat-affected zone of the welded joint of 440MPa grade steel is relatively low, which hinders its further expansion of its application range. In order to broaden the thickness specifications of 440MPa grade steel so that it can meet the 440MPa strength requirements and have good welding performance, it is urgent to apply the method of ultra-low carbon bainite structure design to this system of steel, carry out corresponding research work, solve the problem of the existing 440MPa grade steel thickness specifications and the inability to meet both strength and welding performance, and meet the new requirements of marine engineering. Summary of the invention

[0005] In view of the above analysis, the embodiments of the present invention aim to provide a 440MPa grade ultra-low carbon bainitic steel for marine engineering and a preparation method thereof, which is used to at least solve one of the following problems of the existing 440MPa grade hull steel: 1. The maximum thickness specification adaptability of the existing 440MPa grade hull steel is small; 2. The existing 440MPa grade hull steel has poor welding performance and cannot have good welding performance while meeting the strength requirements.

[0006] The purpose of the present invention is mainly achieved through the following technical solutions:

[0007] The invention provides a 440MPa grade ultra-low carbon bainite steel for marine engineering, the chemical composition of which comprises by weight: C: 0.01%-0.03%, Mn: 0.5%-1.0%, Mo: 0.5%-0.8%, Nb: 0.02%-0.05%, Ni: 1.0%-2.0%, Cr: 0.8%-1.2%, Ti: 0.010%-0.020%, Al: 0.10%-0.30%, and the rest is iron and inevitable impurities.

[0008] Furthermore, the mass ratio of the Ni element to the Al element satisfies: 4≤Ni / Al≤13.

[0009] Furthermore, the microstructure of the steel is granular bainite, and the granular bainite has dispersed and precipitated nano-scale Ni3Al precipitation phase.

[0010] Furthermore, it is characterized in that the maximum thickness specification of the steel is 120 mm.

[0011] The present invention also provides a method for preparing 440MPa grade ultra-low carbon bainitic steel for marine engineering, which is used to prepare the above-mentioned 440MPa grade ultra-low carbon bainitic steel for marine engineering, including molten iron pretreatment-converter smelting-LF refining-RH refining-continuous casting-continuous casting billet heating-controlled rolling and controlled cooling-tempering heat treatment process steps, wherein the RH refining controls the impurity content, by weight: P≤0.008%, S≤0.003%, O≤0.0030%, N≤0.0040%, H≤0.0002%.

[0012] Furthermore, the continuous casting process uses strong cooling in the crystallizer and weak cooling in the secondary cooling zone to control the superheat at 15-25°C, the pulling speed ≤1.1m / min, and enters the slow cooling pit for treatment after continuous casting.

[0013] Furthermore, the continuous casting billet is heated at a temperature of 1200 to 1250° C. and for a heating time of 1.5 to 2 hours.

[0014] Furthermore, the controlled rolling and controlled cooling adopts two-stage rolling, the first stage rolling is rough rolling, the starting rolling temperature is 1150-1180°C, the final rolling temperature is ≥960°C, and the cumulative deformation is ≥65%.

[0015] Furthermore, in the two-stage rolling, the starting rolling temperature is 900-930° C., the finishing rolling temperature is 800-850° C., and the cumulative deformation is ≥30%.

[0016] Furthermore, the tempering heat treatment process is a heating temperature of 600°C to 650°C and a holding time of 2-3h.

[0017] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0018] 1. The present invention provides a new 440MPa grade marine engineering steel alloy component system. The present invention adopts an ultra-low C design and adds Mn, Mo and Nb to suppress the formation of proeutectoid ferrite, so that the alloy system can obtain a uniform bainite structure within a wide cooling rate range. The addition of a higher content of Ni ensures the excellent low-temperature toughness of the steel. The addition of a high Al content ensures the precipitation of a nano-scale Ni3Al phase during the tempering process, providing a strong precipitation strengthening effect.

[0019] 2. The present invention provides a 440MPa grade marine engineering steel with high strength and excellent low-temperature toughness. Due to the refinement of the microstructure of ultra-low carbon bainitic steel and the control of high Ni content (1.0-2.0%), the microstructure of the finally prepared steel is granular bainite with dispersed precipitated nano-scale Ni3Al precipitation phase in the granular bainite, which can adapt to the production of steel plates with a thickness of up to 120mm; it ensures that the steel has good welding performance while meeting the strength requirements, with a transverse impact energy of ≥250J at -84℃ and a longitudinal impact energy of ≥300J at -84℃, and can achieve room temperature welding without preheating, without cold cracks after welding, and the coarse-grained heat-affected zone of the welded joint has an impact energy of ≥200J at -40℃ and CTOD ≥0.35mm.

[0020] 3. The present invention provides a 440MPa grade marine engineering steel with good welding crack resistance and excellent toughness of welded joints. Due to its ultra-low carbon content design, this steel is in the easy welding zone of the Graville diagram, has good crack resistance, and can be welded without preheating at room temperature; at the same time, due to the high Ni content and the control of the microstructure, the impact energy of the coarse-grained heat-affected zone in the welded joint at -40°C is ≥200J.

[0021] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings are only for the purpose of illustrating specific embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0023] Figure 1 This is an optical microscope microstructure diagram of the steel plate in Example 1. DETAILED DESCRIPTION

[0024] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0025] The invention provides a 440MPa grade ultra-low carbon bainite steel for marine engineering, the chemical composition of which comprises by weight: C: 0.01%-0.03%, Mn: 0.5%-1.0%, Mo: 0.5%-0.8%, Nb: 0.02%-0.05%, Ni: 1.0%-2.0%, Cr: 0.8%-1.2%, Ti: 0.010%-0.020%, Al: 0.10%-0.30%, and the rest is iron and inevitable impurities.

[0026] Wherein, the mass ratio of Ni element to Al element satisfies: 4≤Ni / Al≤13.

[0027] The reasons for limiting the composition of the ingot of the 440 MPa grade ultra-low carbon bainite for marine engineering and the method for preparing the same in the present invention are explained below, and only % is used to represent the mass percentage in the composition.

[0028] Carbon (C): C is the most critical factor affecting the structure and performance of bainite. In order to eliminate the damaging effect of C on the weldability and toughness of steel, the C content needs to be reduced to an ultra-low level. According to the current industrial smelting level, the C content is 0.01-0.03%.

[0029] Manganese (Mn): Manganese is an austenite-forming element that can increase the stability of supercooled austenite, help delay the transformation temperature of proeutectoid ferrite, and ensure that the material obtains a better low-temperature transformation structure. The content of Mn is 0.5% to 1.0%.

[0030] Molybdenum (Mo): Mo has a significant solute drag effect, which causes a distinct bend in the supercooled austenite transformation curve and significantly delays high-temperature transformation, separating the upper and lower C curves of steel. The content of Mo is 0.5% to 0.8%.

[0031] Niobium (Nb): Nb can inhibit the deformation and recrystallization behavior of high-temperature austenite, increase the recrystallization temperature, expand the non-recrystallization zone, increase the deformation accumulation during rolling in the non-recrystallization zone, introduce high-density dislocations, and promote microstructure refinement. The content of Nb is 0.02% to 0.05%.

[0032] Nickel (Ni): The Ni element can improve the stability of austenite, reduce the ductile-brittle transition temperature of the material, improve toughness, and is also the key to obtaining thin-film austenite. The Ni content is 1.0% to 2.0%.

[0033] Chromium (Cr): The Cr element can significantly reduce the transformation temperature of bainite, affect the C curve of bainite transformation, and improve the strength of bainitic steel. The addition amount of Cr is 0.8% to 1.2%.

[0034] Titanium (Ti): Ti is a strong nitrogen-fixing element, which combines Ti with N to form TiN, pinning the original austenite in the welding thermal cycle to obtain better toughness of the coarse-grained heat-affected zone. The addition amount of Ti is 0.010% to 0.020%.

[0035] Aluminum (Al): Al plays a deoxidizing role in steel to ensure the purity of molten steel. At the same time, it ensures a certain solid solution aluminum content and forms a dispersed nano-scale Ni3Al phase during the steel tempering process, providing a strong strengthening effect. The addition amount of Al is 0.10%-0.30%.

[0036] The present invention also provides a method for preparing the above-mentioned 440MPa grade ultra-low carbon bainite steel for marine engineering, comprising the following steps:

[0037] Step 1: Hot metal pretreatment: Use low P and low S hot metal for treatment, deep desulfurization of the hot metal, and the slag after desulfurization must be thoroughly removed;

[0038] Step 2: converter smelting + LF refining + RH refining: LF furnace makes white slag to refine molten steel, and adjusts the composition of molten steel to reach the target value; RH furnace refining controls the impurity content;

[0039] Step 3: Continuous casting: Continuous casting uses strong cooling in the crystallizer and weak cooling in the secondary cooling zone, controlling the superheat at 15-25°C, the pulling speed ≤1.1m / min, and entering the slow cooling pit for treatment after continuous casting;

[0040] Step 4: heating the continuous casting billet;

[0041] The continuous casting billet heating temperature is 1200-1250℃, and the heating time is 1.5-2h, to ensure that the high content of alloy elements is fully dissolved into austenite;

[0042] Step 5: controlled rolling and controlled cooling;

[0043] The continuous casting billet is subjected to controlled rolling and controlled cooling, and the controlled rolling adopts a two-stage rolling method: the first stage is rough rolling, with a starting rolling temperature of 1150-1180°C, a final rolling temperature ≥960°C, and a cumulative deformation ≥65%; the second stage is finish rolling, with a starting rolling temperature of 900-930°C, a final rolling temperature of 800-850°C, and a cumulative deformation ≥30%; after rolling, it is air-cooled to room temperature.

[0044] Step 6: Tempering heat treatment: The tempering heating treatment temperature is 600℃~650℃, the insulation time is 2-3h, and air cooling is performed after insulation.

[0045] It should be noted that the impurity content is controlled by RH furnace refining in step 2, wherein P≤0.008%, S≤0.003%, O≤0.0030%, N≤0.0040%, and H≤0.0002%. The step 2 adjusts the composition of the molten steel to reach the target value, i.e., adjusts the composition of the molten steel by LF refining so that the content of the molten steel meets the content of each element required by the present invention.

[0046] It should be noted that the water volume scheme of strong cooling in the crystallizer and weak cooling in the secondary cooling zone in the continuous casting in step 3 can reduce the element segregation in the solidification process and obtain a continuous casting billet with uniform composition and fewer surface defects; the superheat is controlled at 15-25°C, the pulling speed is ≤1.1m / min, and the billet enters the slow cooling pit for treatment after continuous casting.

[0047] It should be noted that the rolling in step 5 is divided into rough rolling and finish rolling, wherein the main purpose of rough rolling is deformation, and rolling is performed in the austenite recrystallization zone. The starting temperature of rough rolling is 1150-1180°C, which can form high-temperature large deformation and penetrate into the core of the billet, which is beneficial to the recrystallization of the core structure; the ending temperature of rough rolling is ≥960°C, 960°C is the termination temperature of austenite recrystallization, and the cumulative deformation is ≥65%, which ensures that the core structure is fully recrystallized, which is beneficial to improving the toughness level of the core structure.

[0048] The purpose of finishing rolling deformation is to regulate the phase transformation process of deformed austenite, so as to obtain fine lath bainite, MA component and film austenite. The starting temperature of finishing rolling is 900-930℃, which is in the non-recrystallization zone of austenite. Starting rolling in the range is conducive to controlling the final rolling, accumulating the deformation in the non-recrystallization zone, and ensuring the control of the final rolling temperature. The final rolling temperature of finishing rolling is 800-850℃, which ensures that the ultra-low carbon bainitic steel is rolled in the non-recrystallization zone of austenite. The accumulated deformation provides sufficient driving force for the subsequent phase transformation, thereby increasing the driving force for the phase transformation of austenite to bainite, and increasing the nucleation rate of ultra-low carbon bainite, so as to obtain fine ultra-low carbon bainite. The accumulated deformation ≥30% can obtain good grain refinement effect; air cooling to room temperature after rolling.

[0049] In step 6, a tempering heat treatment process is performed, the tempering heating treatment temperature is 600°C to 650°C, the holding time is 2-3h, and air cooling is performed after holding to obtain a dispersed nano-scale Ni3Al precipitation phase, which plays a strong precipitation strengthening role and ensures the high strength source of the material.

[0050] The microstructure of the steel prepared by the above preparation method is granular bainite, and the granular bainite has dispersed and precipitated nano-scale Ni3Al precipitation phase.

[0051] The maximum thickness specification of the 440MPa-grade ultra-low carbon bainitic steel for marine engineering prepared by the present invention is 120mm, the yield strength is ≥440Mpa (such as 462-497MPa), the tensile strength is ≥595MPa (such as 596-621MPa), the transverse impact energy at -84°C is ≥250J, the longitudinal impact energy at -84°C is ≥300J, welding without preheating at room temperature can be achieved, cold cracks do not appear after welding, the coarse-grained heat-affected zone of the welded joint has an impact energy of -40°C of ≥200J, and CTOD is ≥0.35mm.

[0052] The advantages of the precise control of the chemical composition, content and preparation process parameters of the present invention will be demonstrated below with specific examples.

[0053] Example 1

[0054] A 440MPa grade ultra-low carbon bainitic steel for marine engineering, the chemical composition of which comprises by weight: C: 0.01%, Mn: 1.0%, Mo: 0.68%, Nb: 0.03%, Ni: 2.0%, Cr: 0.8%, Ti: 0.01%, Al: 0.3%, and the remainder is iron and unavoidable impurities;

[0055] Ni / Al is 6.67, satisfying 4≤Ni / Al≤13.

[0056] The preparation method comprises the following steps:

[0057] Step 1: Hot metal pretreatment:

[0058] Use low P and low S molten iron for treatment, deeply desulfurize the molten iron, and thoroughly remove the slag after desulfurization.

[0059] Step 2: Converter smelting + LF refining + RH refining:

[0060] RH refining controls the impurity content: P: 0.0065%, S: 0.0026%, O: 0.0023%, N: 0.0017%, H: 0.00012%.

[0061] Step 3: Continuous Casting:

[0062] A water volume scheme of strong cooling in the crystallizer and weak cooling in the secondary cooling zone was adopted, with a superheat of 20°C and a pulling speed of 1.0m / min. After continuous casting, the casting entered the slow cooling pit for treatment.

[0063] Step 4: Heating the continuous casting billet

[0064] The continuous casting billet is heated and kept warm at a temperature of 1250°C for 1.5 hours;

[0065] Step 5: controlled rolling and controlled cooling;

[0066] The rolling adopts controlled rolling and controlled cooling process, which is divided into two stages: rough rolling and finish rolling. The starting temperature of rough rolling is 1150℃, the ending temperature of rough rolling is 965℃, and the cumulative deformation of rough rolling is 67%; the starting temperature of finish rolling is 900℃, the ending temperature of finish rolling is 800℃, and the cumulative deformation of finish rolling is 30%. After finish rolling, the steel plate is air-cooled to room temperature.

[0067] Step 6: Tempering heat treatment:

[0068] The tempering heating treatment temperature is 630°C, the holding time is 2h, and air cooling is performed after holding.

[0069] The 440MPa ultra-low carbon bainite steel plate prepared in this embodiment has a thickness of 120mm and a microstructure of granular bainite, in which there is dispersed and precipitated nano-scale Ni3Al precipitate phase, such as Figure 1 shown.

[0070] The mechanical properties are: yield strength is 486MPa; tensile strength is 607MPa; transverse impact energy at -84℃ is 307J, and longitudinal impact energy at -84℃ is 326J; no cracks occur when welding without preheating at room temperature (25℃), the impact energy of the coarse-grained heat-affected zone of the weld joint at -40℃ is 258J, and the CTOD is 0.35mm.

[0071] Example 2

[0072] A 440MPa grade ultra-low carbon bainitic steel for marine engineering, the chemical composition of which comprises by weight: C: 0.03%, Mn: 0.81%, Mo: 0.8%, Nb: 0.02%, Ni: 1.21%, Cr: 1.20%, Ti: 0.02%, Al: 0.1%, and the rest is iron and unavoidable impurities.

[0073] Ni / Al is 12.1, satisfying 4≤Ni / Al≤13.

[0074] The preparation method comprises the following steps:

[0075] Step 1: Hot metal pretreatment:

[0076] Use low P and low S molten iron for treatment, deeply desulfurize the molten iron, and thoroughly remove the slag after desulfurization.

[0077] Step 2: Converter smelting + LF refining + RH refining:

[0078] RH refining controls the impurity content: P: 0.0064%, S: 0.0024%, O: 0.0021%, N: 0.0037%, H: 0.00013%.

[0079] Step 3: Continuous Casting:

[0080] A water volume scheme of strong cooling in the crystallizer and weak cooling in the secondary cooling zone was adopted, with a superheat of 18°C ​​and a pulling speed of 1.1m / min. After continuous casting, the casting entered the slow cooling pit for treatment.

[0081] Step 4: Continuous casting billet heating:

[0082] The continuous casting billet is heated and kept warm at a temperature of 1200°C for 2 hours;

[0083] Step 5: Controlled rolling and controlled cooling:

[0084] The rolling adopts controlled rolling and controlled cooling process, which is divided into two stages: rough rolling and finish rolling. The starting temperature of rough rolling is 1180℃, the ending temperature of rough rolling is 960℃, the cumulative deformation of rough rolling is 65%, the starting temperature of finish rolling is 930℃, the ending temperature of finish rolling is 850℃, the cumulative deformation of finish rolling is 37%. After finish rolling, the steel plate is air-cooled to room temperature.

[0085] Step 6: Tempering heat treatment:

[0086] The tempering heating treatment temperature is 600°C, the holding time is 3h, and air cooling is performed after holding.

[0087] The 440MPa grade ultra-low carbon bainitic steel plate prepared in this embodiment has a thickness of 100mm and a microstructure of granular bainite with dispersed and precipitated nano-scale Ni3Al precipitate phase in the granular bainite.

[0088] The mechanical properties are: yield strength is 497MPa; tensile strength is 621MPa; transverse impact energy at -84℃ is 294J, and longitudinal impact energy at -84℃ is 332J; no cracks occur when welding without preheating at room temperature (25℃), the impact energy of the coarse-grained heat-affected zone of the weld joint at -40℃ is 201J, and the CTOD is 0.36mm.

[0089] Example 3

[0090] A 440MPa grade ultra-low carbon bainitic steel for marine engineering, the chemical composition of which comprises by weight: C: 0.02%, Mn: 0.5%, Mo: 0.5%, Nb: 0.05%, Ni: 1.00%, Cr: 0.98%, Ti: 0.015%, Al: 0.24%, and the rest is iron and unavoidable impurities.

[0091] Ni / Al is 4.17, satisfying 4≤Ni / Al≤13.

[0092] The preparation method comprises the following steps:

[0093] Step 1: Hot metal pretreatment:

[0094] Use low P and low S molten iron for treatment, deeply desulfurize the molten iron, and thoroughly remove the slag after desulfurization.

[0095] Step 2: Converter smelting + LF refining + RH refining:

[0096] RH refining controls the impurity content: P: 0.0071%, S: 0.0026%, O: 0.0025%, N: 0.0037%, H: 0.00017%.

[0097] Step 3: Continuous Casting:

[0098] A water volume scheme of strong cooling in the crystallizer and weak cooling in the secondary cooling zone was adopted, with a superheat of 25°C and a pulling speed of 1.0m / min. After continuous casting, the casting entered the slow cooling pit for treatment.

[0099] Step 4: Continuous casting billet heating:

[0100] The continuous casting billet is heated and kept warm at a temperature of 1230°C for 2 hours;

[0101] Step 5: Controlled rolling and controlled cooling:

[0102] The rolling adopts controlled rolling and controlled cooling process, which is divided into two stages: rough rolling and finish rolling. The starting temperature of rough rolling is 1170℃, the ending temperature of rough rolling is 970℃, the cumulative deformation of rough rolling is 69%, the starting temperature of finish rolling is 915℃, the ending temperature of finish rolling is 820℃, the cumulative deformation of finish rolling is 30%. After finish rolling, the steel plate is air-cooled to room temperature.

[0103] Step 6: Tempering heat treatment:

[0104] The tempering heating treatment temperature is 630°C, the holding time is 2h, and air cooling is performed after holding.

[0105] The 440MPa grade ultra-low carbon bainitic steel plate prepared in this embodiment has a thickness of 80mm, and its microstructure is granular bainite with dispersed and precipitated nano-scale Ni3Al precipitate phase in the granular bainite.

[0106] The mechanical properties are: yield strength is 462MPa; tensile strength is 596MPa; transverse impact energy at -84℃ is 291J, and longitudinal impact energy at -84℃ is 342J; no cracks occur when welding without preheating at room temperature (25℃), the impact energy of the coarse-grained heat-affected zone of the weld joint at -40℃ is 209J, and the CTOD is 0.36mm.

[0107] Comparative Example 1

[0108] The chemical composition of the 440MPa grade marine engineering steel in this comparative example comprises, by weight, 0.06% C, 1.5% Mn, 0.05% Nb, 0.5% Ni, 0.2% Cr, 0.015% Ti, 0.02% Al, and the remainder being iron and unavoidable impurities.

[0109] The preparation method and process parameters are the same as those in Example 1.

[0110] The thickness of the steel plate prepared in this comparative example is 80 mm, and the microstructure is composed of ferrite + pearlite.

[0111] The mechanical properties are: yield strength is 396MPa; tensile strength is 499MPa; transverse impact energy at -84℃ is 301J, and longitudinal impact energy at -84℃ is 317J; no cracks occur when welding without preheating at room temperature (25℃), the impact energy of the coarse-grained heat-affected zone of the weld joint at -40℃ is 188J, and the CTOD is 0.20mm.

[0112] Comparative Example 2

[0113] The chemical composition and content of the 440MPa grade marine engineering steel in this comparative example are the same as those in Example 2.

[0114] The preparation method comprises the following steps:

[0115] Step 1: Hot metal pretreatment:

[0116] Use low P and low S molten iron for treatment, deeply desulfurize the molten iron, and thoroughly remove the slag after desulfurization.

[0117] Step 2: Converter smelting + LF refining + RH refining:

[0118] RH refining controls the impurity content: P: 0.0071%, S: 0.0026%, O: 0.0025%, N: 0.0037%, H: 0.00017%.

[0119] Step 3: Continuous Casting:

[0120] A water volume scheme of strong cooling in the crystallizer and weak cooling in the secondary cooling zone was adopted, with a superheat of 25°C and a pulling speed of 1.0m / min. After continuous casting, the casting entered the slow cooling pit for treatment.

[0121] Step 4: Continuous casting billet heating:

[0122] The continuous casting billet is heated and kept warm at a temperature of 1230°C for 2 hours;

[0123] Step 5: Controlled rolling and controlled cooling:

[0124] The rolling adopts controlled rolling and controlled cooling process, which is divided into two stages: rough rolling and finish rolling. The starting temperature of rough rolling is 1150℃, the ending temperature of rough rolling is 950℃, the cumulative deformation of rough rolling is 60%, the starting temperature of finish rolling is 900℃, the ending temperature of finish rolling is 800℃, the cumulative deformation of finish rolling is 20%. After finish rolling, the steel plate is air-cooled to room temperature.

[0125] Step 6: Tempering heat treatment:

[0126] The tempering heating treatment temperature is 550°C, the holding time is 2h, and air cooling is performed after holding.

[0127] The thickness of the steel plate prepared in this comparative example is 100 mm, and the microstructure is granular bainite, in which there is dispersedly precipitated nano-scale Ni3Al precipitate phase.

[0128] The mechanical properties are: yield strength is 427MPa; tensile strength is 531MPa; transverse impact energy at -84℃ is 296J, and longitudinal impact energy at -84℃ is 325J; no cracks occur when welding without preheating at room temperature (25℃), the impact energy of the coarse-grained heat-affected zone of the weld joint at -40℃ is 199J, and the CTOD is 0.33mm.

[0129] Table 1 Chemical composition of steel in the examples and comparative examples (wt, %)

[0130] serial number C Mn Mo Nb Ni Cr Ti Al Ni / Al Example 1 0.01 1.0 0.68 0.03 2.0 0.8 0.01 0.3 6.67 Example 2 0.03 0.81 0.80 0.02 1.21 1.20 0.02 0.10 12.1 Example 3 0.02 0.5 0.5 0.05 1.00 0.98 0.015 0.24 4.17 Comparative Example 1 0.06 1.5 - 0.05 0.5 0.2 0.015 0.02 25 Comparative Example 2 0.03 0.81 0.80 0.02 1.21 1.20 0.02 0.10 12.1

[0131] Table 2 Example and comparative steel preparation process

[0132]

[0133] Table 3 Mechanical properties of steels in examples and comparative examples

[0134]

[0135] It can be seen from the comparative examples and embodiments that the chemical composition of the steel of comparative example 1 does not meet the requirements of the present invention, and the yield strength of the steel finally prepared is lower than 440 MPa, and the welding performance is also much lower than that of the embodiments of the present invention. Although the chemical composition of the steel of comparative example 2 meets the requirements of the present invention, some process parameters in the preparation process do not meet the requirements of the present invention, and the strength and welding performance of the steel finally prepared are lower than those of the embodiments of the present invention.

[0136] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A 440MPa grade ultra-low carbon bainitic steel for marine engineering, characterized in that: The chemical composition includes by weight: C: 0.01% ~ 0.03%, Mn: 0.5% ~ 1.0%, Mo: 0.5% ~ 0.8%, Nb: 0.02% ~ 0.05%, Ni: 1.0% ~ 2.0%, Cr: 0.8% ~ 1.2%, Ti: 0.010% ~ 0.020%, Al: 0.10% -0.30%, and the rest is iron and unavoidable impurities.

2. The 440MPa grade ultra-low carbon bainite steel for marine engineering according to claim 1, characterized in that: The mass ratio of the Ni element to the Al element satisfies: 4≤Ni / Al≤13.

3. The 440MPa grade ultra-low carbon bainite steel for marine engineering according to claim 1, characterized in that: The microstructure of the steel is granular bainite, and the granular bainite has dispersed and precipitated nano-scale Ni3Al precipitation phase.

4. The 440MPa grade ultra-low carbon bainite steel for marine engineering according to claim 1, characterized in that: The maximum thickness specification of the steel is 120 mm.

5. A method for preparing 440MPa grade ultra-low carbon bainite steel for marine engineering, used for preparing the 440MPa grade ultra-low carbon bainite steel for marine engineering according to any one of claims 1 to 4, characterized in that: The invention comprises the following process steps: molten iron pretreatment - converter smelting - LF refining - RH refining - continuous casting - continuous casting billet heating - controlled rolling and controlled cooling - tempering heat treatment. The RH refining controls the impurity content, which is calculated by weight as follows: P≤0.008%, S≤0.003%, O≤0.0030%, N≤0.0040%, and H≤0.0002%.

6. The method for preparing 440MPa grade ultra-low carbon bainite steel for marine engineering according to claim 5, characterized in that: The continuous casting process adopts strong cooling water in the crystallizer and weak cooling water in the secondary cooling zone, controls the superheat to be 15-25°C, and the pulling speed is ≤1.1m / min. After continuous casting, it enters the slow cooling pit for treatment.

7. The method for preparing 440MPa grade ultra-low carbon bainite steel for marine engineering according to claim 6, characterized in that: The continuous casting slab is heated at a temperature of 1200 to 1250° C. and for a heating time of 1.5 to 2 hours.

8. The method for preparing 440MPa grade ultra-low carbon bainite steel for marine engineering according to claim 7, characterized in that: The controlled rolling and controlled cooling adopts two-stage rolling, the first stage rolling is rough rolling, the starting rolling temperature is 1150-1180° C., the final rolling temperature is ≥960° C., and the cumulative deformation is ≥65%.

9. The method for preparing 440MPa grade ultra-low carbon bainite steel for marine engineering according to claim 8, characterized in that: In the two-stage rolling, the starting rolling temperature is 900-930° C., the final rolling temperature is 800-850° C., and the cumulative deformation is ≥30%.

10. The method for preparing 440MPa grade ultra-low carbon bainite steel for marine engineering according to claim 9, characterized in that: The tempering heat treatment process is a heating temperature of 600°C to 650°C and a heat preservation time of 2-3h.